Indonesian Adolescents' Online Opportunities and Risks - Amia Luthfia; Pinckey Triputra; Hendriyani . (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
This research aims to 1) explore the benefits of online (benefits obtained when on the internet) and online risks (risks experienced when on the internet) in adolescents in Jakarta; 2) Test differences in online benefits and online risk based on differences in gender, education level, and school affiliation. This study used a survey method with a multilevel random sampling technique performed on adolescents living in Jakarta aged 12-18 (N = 756). The data analysis technique for this study is descriptive analysis and T-test analysis. The results of the research show that teenagers in Jakarta regularly use the internet every day with relatively high duration. More than 60% of teens benefit online in the medium to the high category, with six types of benefits online: learning, creative participation, social participation, social relations, entertainment, commercial benefits, and personal benefits. Most teens experience online risk in the low category, with three types of risks: content risk, contact risk, and behavioral risk. Other findings, namely: (1) there are significant differences in online risk-based on sex and adolescent education level; (2) significant differences in online benefits are based solely on adolescent education levels. There are no significant differences in online and online risk benefits based on school affiliation (non-religious schools and religion-based schools). This research contributes to the importance of distinguishing online benefits and online risks from adolescent education levels.